Heavy Drinking and Polydrug Use among College Students - O’Grady, Kevin E. (2008)
Excessive alcohol consumption is a serious problem on college campuses but may not be adequately captured by traditional methods of defining binge drinking. This study examined a new approach to categorizing alcohol use and its relationship with illicit drug use. A survey was administered to 484 college students ages 18 to 25. Drinkers were divided into three groups based on the number of typical drinks consumed per day: “light”—1 to 4 (n=182); “moderate”—5 to 9 (n=173); and “heavy”—10+ (n=56). Heavy drinkers could be differentiated from moderate and light drinkers on age of onset of alcohol use, illicit drug use, and frequency of illicit drug use. A binary categorization of “binge” vs. “nonbinge” drinking may obscure important differences within binge drinkers. These findings have implications for prevention, as well as clinical risk assessment of college student drinkers for adverse consequences of concomitant alcohol and illicit drug consumption.